PENGARUH RETURN ON ASSET, CURRENT RATIO, DEBT TO ASSET RATIO DAN TOTAL ASSET TURNOVER TERHADAP HARGA SAHAM - Jonathan Alexander Ceme Sada; Muhammad Jusman Syah (Taksasila Edukasi Insani, 2025)
This research aims to determine the effect of Return on Asset, Current Ratio, Debt to Asset Ratio, Total Asset Turnover on Stock Price. The population used in this study are Automotive Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2020-2024 Period. This study uses secondary data and jenuh sampling techniques, so that a population of 16 companies and a sample consisting of 11 Automotive manufacturing companies listed on the Indonesia Stock Exchange for the 2020-2024 Period. The analysis used in this research is multiple linear regression analysis which is processed by the Statistical Program for Social Science (SPSS) version 26 program. The results showed that Return on assets and Total Asset Turnover had an effect on stock prices, while Current Ratio and Debt to Asset Ratio had no effect on stock prices. Keywords :Return on Asset, Current Ratio, Debt to Asset Ratio, Total Asset Turnover and Stock Price.